Taxonomic revision of Idesia (Salicaceae) from China - Wu, Xue-Xue; Xu, Chao; Liang, Tong-Jun; Li, Xin (Phytotaxa, 2025)
The relationship among the species of the genus Idesia Maximowicz is unclear. Related literature and books record one species in this genus: Idesia polycarpa Maxim. Five varieties are identified: I. polycarpa var. vestita Diels, Idesia polycarpa var. latifolia Diels, Idesia polycarpa var. intermedia Pampanini, I. polycarpa var. fujianensis (G.S. Fan) S.S. Lai, and I. polycarpa var. longicarpa S.S. Lai, which are distributed in China. We extensively examined specimens and conducted field investigations, comparing the taxonomic characteristics of four taxa within the Idesia genus: I. polycarpa, I. polycarpa var. vestita, I. polycarpa var. fujianensis, and I. polycarpa var. longicarpa. We utilised principal component analysis (PCA) and scanning electron microscopy (SEM) to assess their distinctive features while analysing their geographical distribution based on sample data points. Additionally, we conducted phylogenetic relationship reconstructions among these taxa. The results showed that seven identification characters, such as leaf length and width, fruit length and diameter, and fruit stalk length of the four taxa of Idesia, formed one group in the scatter plot. The measurement of related quantitative traits of I. polycarpa var. vestita, I. polycarpa var. longicarpa, and I. polycarpa var. fujianensis showed that they were all within the range of variation of I. polycarpa. The results of electron microscope scanning showed that the leaf epidermis pattern, stomata shape, and inner edge of the outer arch of stomata were similar among the four. Only the morphology of the waxy layer on the back of the cotyledons of I. polycarpa var. fujianensis differed from that of the other three. The geographic distribution areas of the four groups also overlapped. The phylogenetic tree topology of Idesia, obtained by the maximum likelihood method (ML) and Bayesian inference method (BI), was consistent, indicating that the genus Idesia is monophyletic and divided into three main clades. I. polycarpa and I. polycarpa var. vestita were nonmonophyly. Based on the type specimens, original literature, and our research results, we propose that I. polycarpa var. vestita, I. polycarpa var. fujianensis, and I. polycarpa var. longicarpa should be reduced to a synonym of I. polycarpa.